Resting state frontal alpha asymmetry predicts emotion regulation difficulties in impulse control. (1st June 2020) - Zhang, Jing; Hua, Yan; Xiu, Lichao; Oei, Tian Po; Hu, Ping
Highlights: Decreased left frontal activity predicates more emotion regulation difficulties. Frontal alpha asymmetry explains impulse control difficulties. Frontal alpha asymmetry does not explain all dimensions of DERS. Abstract: Failure in emotion regulation would cause barriers to individuals' adaptive behavior, which negatively affect a human's happy and healthy life. Recent studies indicate that decreased activity of the left frontal cortex can be treated as a neural marker of emotion disorders. The present study examined how resting state frontal alpha asymmetry could predict emotion regulation difficulties and related dimensions by resting state electroencephalogram (EEG) recordings, and a measure of the Difficulties in Emotion Regulation Scale (DERS). Eighty participants completed the resting state EEG recording and DERS ratings. Results revealed that after controlling for gender and depression scores, those participants with higher left frontal activity than the right frontal activity in the resting state have less difficulties in everyday emotion regulation, especially in the dimension of impulse control. However, there was no relation pattern with other dimensions of DERS. This study provided evidence that resting state frontal alpha asymmetry could predict emotion regulation difficulties, mainly in impulse control.